Evaluation of the biomethane potential of solid fish waste - Eiroa, M. (2012)
Manufacturing processes in fish canning industries generate a considerable amount of solid waste that can be digested anaerobically. The aim of this research was to study the biochemical methane potential of different solid fish waste. For tuna, sardine and needle fish waste, around 0.47 g COD–CH4/g CODadded was obtained in batch experiments with 1%TS; whereas for mackerel waste, the methane production attained 0.59 g COD–CH4/g CODadded. The increase in the waste/inoculum ratio, from 1.1–1.3 to 2.8– 3.3 g VSwaste/g VSinoculum, led to overload due to VFA and LCFA accumulation. Afterward, co-digestion assays of fish waste with gorse were undertaken but the biochemical methane potential did not improve.